Pengaruh Aktivitas Kewirausahaan Terhadap Pertumbuhan Usaha Pengolahan Sampah di Bank Sampah Sawangan, Depok - Sari, Silvia; Septiowati, Rini; Saputri, Sevty Wahiddirani (Departmen of Agribusiness, Economics and Management Faculty, Bogor Agricultural University, 2021)
One of the alternatives to reduce waste in Indonesia is the establishment of a Waste Bank. The role of waste bank actors is not the same as collectors or scavengers, they are expected to have entrepreneurial and personal characteristics. The purpose of this study is to analyze the forming factors of entrepreneurial activity in waste banks that contribute to the growth of a sustainable waste processing business. This research was conducted in Sawangan Depok. The first research stage collected primary data using a questionnaire on 111 active waste bank actors using the purposive sampling technique, then analyzed the data using Structural Equation Modeling (SEM). The results showed that the goodness fit criteria were met and the measurement variables in the model had good reliability (CR≥0,70, VE≥0,50). The entrepreneurial activities of waste bank actors are most influenced by entrepreneurial characteristics (γ = 0,70) and resources (γ = 0,63). The entrepreneurial characteristics of the waste bank actors are well shaped by motivation (λ = 0,40), risk (λ = 0,49), and innovation (λ = 1,00). The implication is that to grow a sustainable waste bank requires an innovative character for the waste bank actors.